2017
DOI: 10.4172/2329-8731.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Lindane Shampoo for Head Lice Treatment among Female Secondary School Students in Jeddah, Saudi Arabia: An Interventional Study

Abstract: Background: We aimed to determine the prevalence of head lice infestation, effectiveness of over-the-counter treatment options, and the effectiveness and safety of lindane shampoo among female Saudi Arabian secondary school students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…SS was found in 37% of the samples, and RR was found in 63% of the samples. A previous study from Saudi Arabia found that 69% of people did not respond to pyrethrin-containing pediculicide shampoo; these findings are similar to ours, though the non-responders included RS and SS genotypes ( Abdullah & Kaki, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…SS was found in 37% of the samples, and RR was found in 63% of the samples. A previous study from Saudi Arabia found that 69% of people did not respond to pyrethrin-containing pediculicide shampoo; these findings are similar to ours, though the non-responders included RS and SS genotypes ( Abdullah & Kaki, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…Infestation with head lice is a public health issue in many regions of the world ( Al-Saeed et al, 2006 , Motovali-Emami et al, 2008 , Toloza et al, 2009 , Shayeghi et al, 2010 , Bosely and El-Alfy, 2011 ; Değerli et al, 2013 , Mohammadi-Azni, 2014 , Al-Zanbagi and Al-Hashdi, 2015 , Al-Zanbagi and Al-Hashdi, 2016 , Al Abdullah and Kaki, 2017 , Nategh et al, 2018 , Alberfkani and Mero, 2020 ). In this study, the overall prevalence of head lice infestation was 77.69% among school workers which agreed with all previous studies on lice infecting school children; this percentage could be related to the common nature of the school workers and their way of social life, poor personal hygiene, and the continuous sharing of hair combs and other hair items with family members and most of the barbers and make up places.…”
Section: Discussionmentioning
confidence: 99%
“…In many developed countries, the prevalence of Pediculosis capitis increased in the last two decades despite the improvement of hygienic conditions and the effective methods of treatment ( Burgess, 2004 , Kim et al, 2004 ). Few studies were conducted in Saudi Arabia about the awareness, attitude, and practices of the head lice and its treatment ( El-Mehmady, 1995 ; Bahamdan et al, 1996 , Al-Saeed et al, 2006 , Bosely and El-Alfy, 2011 , AL-Megrin, 2015 ; Al-Zanbagi and Al-Hashdi, 2016 , Al Abdullah and Kaki, 2017 , Assaedi et al, 2018 , Moussa et al, 2018 ). The control of lice infestation continues to be a difficult problem due to the uncontrolled modes of transmission and the relative deficiency of the available treatments ( Combescot-Lang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%